MODELING OF URBAN GRAVITY ZONES AND HIERARCHY OF ADMINISTRATIVE CENTERS IN BOSNIA AND HERZEGOVINA USING THE HUFF MODEL“ - Ivan Marić; Aida Avdić; Ante Šiljeg (Geodetski Glasnik)
This research applies the Huff model in delineating urban gravitational zones (UGZs) and hierarchy ranking of administrative centers in Bosnia and Herzegovina. Based on the attributes of travel time (min) and attractiveness, i. e. the mass of the city, gravitational attraction raster models were derived for each center. UGZs were compared with the official administrative units - cantons (FB&H) and regions (RS) based on area and shape attributes. Hierarchy of centers according to UGZs is compared with the official data. Some discrepancies have been observed between theoretical UGZs and actual administrative regions, mostly due to socio-political factors that significantly influence urban development pattern and social dynamics. It was found that polygons of official administrative units are more complex regarding shape than UGZs, indicating a more fragmented structure. The results showed that the average relative difference in area of official administrative units and the UGZs is 60.94%. Out of 16 administrative centers, 10 (62.5%) of them have the same hierarchical rank in both models, while the other six centers differ. An important feature of Huff method is that it uses a spatial model with exact data (parameters) and formulas rather than subjective procedures.